Investigations of nano-crystalline Sr0.5Ba0.5Nb2O6 and bulk ceramics synthesized by a polymerization method using PEG400. Issue 4 (April 2019) - Köferstein, Roberto; Oehler, Florian; Ebbinghaus, Stefan G.
Abstract: Nano-crystalline Sr0.5 Ba0.5 Nb2 O6 was synthesized by a one-pot method using PEG400 and citric acid. Calcination of the (Sr, Ba, Nb)-gel at 600 °C leads to Sr0.5 Ba0.5 Nb2 O6 with a crystallite size of 24(2) nm and a specific surface area of 38.5(10) m 2  g −1 . Sintering up to 1325 °C leads to ceramics with globular or irregular-shaped grains and average grain sizes between 1.3 and 2.4 μm, whereas higher temperatures lead to a rod-like microstructure. The indirect allowed optical band gap varies between 3.70(5) and 3.29(5) eV. Dielectric measurements show a diffuse phase transition and weak relaxor properties. The maximum of the permittivity occurs between 116 and 147 °C. The frequency dependence of the impedance can be well described by one or two RC-circuits depending on sintering temperature. The melting temperature is determined as 1506(7) °C with ΔHf  = 140(20) kJ mol −1 . The average linear thermal expansion coefficient is found to be 10.5(5)⋅10 −6  K −1 .